Long-term outcomes of an extracorporeal irradiated autograft for limb salvage operations in musculoskeletal tumours: over ten years' observation. (September 2019) - Oike, N.; Kawashima, H.; Ogose, A.; Hatano, H.; Ariizumi, T.; Kaidu, M.; Aoyama, H.; Endo, N.
Abstract : Aims: We analyzed the long-term outcomes of patients observed over ten years after resection en bloc and reconstruction with extracorporeal irradiated autografts Patients and Methods: This retrospective study included 27 patients who underwent resection en bloc and reimplantation of an extracorporeal irradiated autograft. The mean patient age and follow-up period were 31.7 years (9 to 59) and 16.6 years (10.3 to 24.3), respectively. The most common diagnosis was osteosarcoma (n = 10), followed by chondrosarcoma (n = 6). The femur (n = 13) was the most frequently involved site, followed by the tibia (n = 7). There were inlay grafts in five patients, intercalary grafts in 15 patients, and osteoarticular grafts in seven patients. Functional outcome was evaluated with the Musculoskeletal Tumor Society (MSTS) scoring system. Results: There were no recurrences in the irradiated autograft and the autograft survived in 24 patients (88.9%). Major complications included nonunion (n = 9), subchondral bone collapse (n = 4), and deep infection (n = 4). Although 34 revision procedures were performed, 25 (73.5%) and four (11.8%) of these were performed less than five years and ten years after the initial surgery, respectively. The mean MSTS score at the last follow-up was 84.3% (33% to 100%). Conclusion: Considering long-term outcomes, extracorporeal irradiated autograft is an effective method of reconstruction for malignant musculoskeletal tumours Cite this article: Bone Joint J 2019;101-B:1151–1159